2012
DOI: 10.1029/2012gl054094
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the regional stress field in central Japan during the late Quaternary inferred from the stress inversion of the active fault data

Abstract: We analyzed 169 geological fault‐slip data from 37 active faults in central Japan to investigate the late Quaternary stress field stability. Modern stress states have been documented with unprecedented accuracy; however, their stability over time scales beyond instrumental observations is inadequately understood. Because the stress field has changed in the geological past, we compared present stress conditions in central Japan, determined from geophysical observations, with conditions determined by inverting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…They found that the direction of the σ 1 -axis tends to be ESE-WNW and that the stress ratio is close to 1.0, indicating σ 2 ≈ σ 3 , which suggests that the stress field in central Japan has been uniform and stable over the past approximately 10 5 years. The direction of the σ 1 -axis and the stress ratio obtained by Tsutsumi et al (2012) are consistent with the results in this study. Hiramatsu and Iidaka (2015) obtained a spatial distribution of S-wave splitting parameters and found that the observed polarization orientation ranges from E-W to NW-SE, which is consistent with the direction of the σ 1 -axis obtained in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…They found that the direction of the σ 1 -axis tends to be ESE-WNW and that the stress ratio is close to 1.0, indicating σ 2 ≈ σ 3 , which suggests that the stress field in central Japan has been uniform and stable over the past approximately 10 5 years. The direction of the σ 1 -axis and the stress ratio obtained by Tsutsumi et al (2012) are consistent with the results in this study. Hiramatsu and Iidaka (2015) obtained a spatial distribution of S-wave splitting parameters and found that the observed polarization orientation ranges from E-W to NW-SE, which is consistent with the direction of the σ 1 -axis obtained in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Terakawa and Matsu'ura (2010) found that compressional stress is dominant in central Japan and that its axis is oriented E-W, which is also consistent with our results. Tsutsumi et al (2012) inverted 169 fault-slip data points from 37 active faults in the eastern part of the Southwest Japan arc, including the Nobi fault area. They found that the direction of the σ 1 -axis tends to be ESE-WNW and that the stress ratio is close to 1.0, indicating σ 2 ≈ σ 3 , which suggests that the stress field in central Japan has been uniform and stable over the past approximately 10 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The northern Tohoku region and the Kinki region are similar in that the long‐term E‐W compression generates inland earthquakes and interplate earthquakes drag the regions toward the SSE. On the other hand, the two regions differ in that in the Kinki region, about half of inland active faults are strike slip suggesting that the minimum principal stress ranges from horizontal to vertical in the basic stress field [ Tsutsumi et al ., ], and the focal mechanisms of inland earthquakes are more sensitive to the stress change. In contrast, the elastic stress change due to interplate earthquakes is larger in the northern Tohoku region (0.5–1.0 MPa for the 2011 earthquake) than that in the central Kinki region (0.1–0.3 MPa for the interplate earthquakes along the Nankai Trough), which explains why the change in focal mechanism occurred in the Tohoku region.…”
Section: Discussionmentioning
confidence: 99%
“…The stress regime in central Japan is characterized by E-W or ESE-WNW directed maximum horizontal principal stresses (e.g., Seno, 1999;Terakawa and Matsu'ura, 2010;Townend and Zoback, 2006;Tsutsumi et al, 2012). Seno (1999) modeled this stress regime using a simplified framework of the regional plate configuration and driving forces, and showed that the regime can be explained by ridge push, slab pull, and along-arc variations in differential forces caused by the heterogeneity of the crust-plate structure in this area.…”
Section: Tectonic Framework and Stress Regime Around The Nobi Fault Smentioning
confidence: 98%